Cyclin D1 gene polymorphism as a risk factor for squamous cell carcinoma of the upper aerodigestive system in non-alcoholics - Nishimoto, I. N.; Pinheiro, N. A.; Rogatto, Silvia Regina [UNESP]; Carvalho, A. L.; Simpson, A. J.; Caballero, O. L.; Kowalski, L. P. (Elsevier B.V., 2004)
Squamous cell carcinoma of the upper aerodigestive tract (UADT) is associated with environmental factors, especially tobacco and alcohol consumption. Genetic factors, including cyclin D1 (CCND1) polymorphism have been suggested to play an important rote in tumorigenesis and progression of UADT cancer. To investigate the relationship between CCND1 polymorphism on susceptibility for UADT cancers, 147 cancer and 135 non-cancer subjects were included in this study. CCND1 genotype at codon 242(G870A) in exon 4 was undertaken using denaturing high performance liquid chromatography (DHPLC) and DNA sequencing. Significant odds ratio (OR) of the AA + GA genotypes [OR = 7.5 (95% Cl: 1.4-39.7)] was observed in non-drinkers but for non-smokers a non-significant [OR = 5.4 (95% Cl: 0.9-31.4)] was found in the adjusted model. These results suggest that allele A may be a risk factor for UADT cancer, especially in non-alcoholics. However, further epidemiological studies are needed to establish the exact role of CCND1 polymorphism and the development of UADT cancers. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: UADT; CCND1 polymorphism; risk factor; cancer; upper aerodigestive system